2006
DOI: 10.1152/japplphysiol.01039.2005
|View full text |Cite
|
Sign up to set email alerts
|

Circulatory galanin levels increase severalfold with intense orthostatic challenge in healthy humans

Abstract: The purpose of this study was to test the hypothesis that plasma galanin concentration (pGal) is regularly increased in healthy humans with extensive orthostatic stress. Twenty-six test persons (14 men, 12 women) were brought to an orthostatic end point via a progressive cardiovascular stress (PCS) protocol consisting of 70 degrees head-up tilt plus increasing levels of lower body negative pressure until either hemodynamically defined presyncope or other signs of orthostatic intolerance occurred (nausea, clamm… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
42
2

Year Published

2007
2007
2019
2019

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 17 publications
(45 citation statements)
references
References 31 publications
1
42
2
Order By: Relevance
“…there was an increase in plasma GAL for rVVS patients during HUTT, regardless whether they developed syncope or not. Our data are thus in a partial conflict with those of Bondanelli et al Elsewhere it has been demonstrated in healthy individuals that GAL plasma levels increase severalfold with orthostatic stress in the presyncopal phase 3 , which further questions the reproducibility of the results of Bondanelli. A possible explanation for this conflict may be the absence of a unique GAL secretion pattern.…”
Section: Resultscontrasting
confidence: 99%
See 1 more Smart Citation
“…there was an increase in plasma GAL for rVVS patients during HUTT, regardless whether they developed syncope or not. Our data are thus in a partial conflict with those of Bondanelli et al Elsewhere it has been demonstrated in healthy individuals that GAL plasma levels increase severalfold with orthostatic stress in the presyncopal phase 3 , which further questions the reproducibility of the results of Bondanelli. A possible explanation for this conflict may be the absence of a unique GAL secretion pattern.…”
Section: Resultscontrasting
confidence: 99%
“…Both peptides are known to affect vasovagal response. However, their specific roles are unclear 3,4 . Thus the rationale of this study was to ascertain whether either one or both peptides are substantially involved in the course of VVS.…”
Section: Introductionmentioning
confidence: 99%
“…Combined HUT and LBNP have been used-sometimes as a surrogate for centrifuge rides-to study features of cardiovascular and humoral regulation under severe stress conditions and to induce presyncopal signs and symptoms [6,20,24,30]. Previously, we have also used combined orthostatic stress to observe sex-based differences in the neurohormone galanin [18] and cardiovascular effects of Chinese herbs [9]. The advantage of combined graded orthostatic stress is the absence of medication to induce syncope.…”
Section: Discussionmentioning
confidence: 99%
“…As soon as presyncopal signs or symptoms occurred, the table was brought back to 0°and LBNP was stopped at once. The criteria of presyncope were any of the following: (a) arterial blood pressure drop below systolic 80 mmHg or by C25 mmHg/minute, diastolic by C15 mmHg/minute, and/ or heart rate decrease by C15 bpm, (b) lightheadedness, dizziness, visual disturbances, nausea, stomach awareness, clammy skin, excessive sweating, or skin pallor [18].…”
Section: Protocolmentioning
confidence: 99%
“…Extreme cardiovascular stress can also be achieved with a combination of head up tilt and lower body 'negative' pressure (El-Bedawi and Hainsworth 1994;Hinghofer-Szalkay et al 2006;Goswami et al 2009). This model provides easy access to data mirroring individual features of neuronal and endocrine blood pressure defence during circumstances of critical central hypovolemia.…”
Section: Brain Perfusionmentioning
confidence: 99%